Debido proceso probatorio y derecho de contradicción probatoria en el trámite de revisión de fallos de tutela (2014)
Evidence due process, in its evidence contradiction aspect, is a fundamental right demandable in the revision procedures of “tutela” sentences by Colombia Constitutional Court, in spite of the own celerity of the Constitutional Court. In the research from which this article resulted, it was established that in (5) five files of “tutela” sentences revision related to the right to minimum right for fresh water for subjects of special constitutional protection, the Constitutional Courtseriously restricted the contradiction right of evidence with no justification at all, which make constitute an observance of evidence warranties of fundamental right to the due process and specially to the right of evidence contradiction